PSII-5 Corn-expressed phytase improved the growth performance, nutrients digestibility and bone mineral density of nursery pigs fed with low protein, calcium and phosphorous diets. (5th December 2019) - Shili, Cedrick N; Broomhead, Jon; Pezeshki, Adel
Abstract: Feeding pigs with moderately reduced crude protein (CP), calcium (Ca) and phosphorous (P) diets may be an effective strategy to decrease the nutrients excretion; however, this practice can negatively impact the growth performance. Thus, there is an urgent need to improve the utilization of nitrogen, Ca and P in pigs. The objective was to assess the effect of phytase (GraINzyme ® ) on growth performance, nutrient digestibility, body composition, and serum amino acid profile in pigs fed with low-CP, -Ca and -P diets. Following 2-week acclimation period, forty-eight weaned barrows weighing ~ 10 kg were subjected to one of following groups (n = 8/group) for 4 weeks: A) standard-protein (~24% CP), B) low-protein (~13% CP), C) low-protein+2000 FTU/kg phytase, D) low-protein+4000 FTU/kg phytase, E) low-protein, -Ca and -P+2000 FTU/kg phytase and F) low-protein, -Ca and -P+4000 FTU/kg. The data were analyzed by univariate GLM with Tukey's post-hoc test (SPSS ® ). Feed intake and body weight were measured daily and weekly, respectively. At week 4, feed, fecal and blood samples were collected and pigs were scanned using dual-energy X-ray absorptiometry. Pigs fed with diets C and F had higher average daily gain than those fed with diet B (P < 0.05). The apparent fecal digestibility of Ca and P and bone mineral density was higher for diets D and F than diet B (P < 0.05). Pigs fed diet C and F had a higher fat mass than those fed with diet B (P < 0.05). Serum lysine, methionine and threonine of pigs fed with diets B-F were greater than those received diet A (P < 0.05). In conclusion, our data provide evidence that phytase, in particular at 4000FTU/kg, improved the growth performance, digestibility of Ca and P and bone mineral density in pigs fed with moderately low protein diets with reduced Ca and P content.